A new method to reduce motion artifact in electrocardiogram based on an innovative skin-electrode impedance model. (July 2022) - Gan, Yajian; Rahajandraibe, Wenceslas; Vauche, Remy; Ravelo, Blaise; Lorriere, Nominoë; Bouchakour, Rachid
Abstract: The electrocardiogram (ECG) is sensitive to human body motions when it is measured with dry metal electrodes. A common hypothesis in previous literature dealing with these subjects postulate that this is due to the skin-electrode impedance variability. This paper aims to verify this hypothesis by investigating the origin of the noise in the ECG signal and finding suitable solutions to reduce this disturbance. For this reason, experiments are proposed here to explore the relationship between the skin-electrode impedance and the ECG for several motions. Results demonstrate that the noise due to human body motions in ECG equally comes from the electrochemical equilibrium break of the reduction–oxidation reaction at the skin-electrode interface. Moreover, it has been shown that motions lead to sweat thickness variations and equally to skin-electrodes capacitance variations. To model this phenomenon, an electrical model based on a variable capacitor is introduced. Finally, a significant noise reduction solution based on the monitoring of this capacitor is proposed.